Topology and Quality of Life of Cutaneous T-Cell-Lymphomas: A Cross-sectional Study of 153 Patients - Inga Hansen-Abeck; Larissa Kölln; Isabel Heidrich; Finn Abeck; Julian Kött; Stefan W Schneider; Glenn Geidel; Nina Booken (Clinical and Experimental Dermatology, 2026)
Abstract Introduction Cutaneous T-cell lymphomas (CTCL) comprise a clinically, histologically, and molecularly heterogeneous group of subtypes. They fulfil aspects of both chronic and malignant skin conditions and may thus affect health-related quality of life (HRQL) in various ways. To date, there is little information known about the topology of CTCL patients in routine care. Objectives This study aims to characterize the frequency and distribution of body sites affected by CTCL in routine care and to analyze the impact on HRQL. Methods Cross-sectional survey study as part of the routine care at a University Medical Center. Topical distribution was identified with a detailed grid scheme filled by the patient and the affected body surface area (BSA) was recorded by the physician. Skindex-29 measured HRQL. Results 153 patients with CTCL were included, with a mean age of 59.5 ± 16.5 years and a majority of male patients (61.4%). The mean number of grids marked was 129.2, corresponding to 12.7% of the BSA, and the most frequently affected body areas were thighs, back, and lower legs. Skindex-29 revealed that HRQL in CTCL patients is impaired on a mild level, with a mean of 27.5 ± 21.3. Patients with involvement of the visible or genital area showed a significantly poorer HRQL. Overall, 70% of patients reported relevant pruritus (NRS ≥3), which was strongly associated with worse HRQL, independent of localization. Linear regression analysis revealed a significant correlation between an increased impairment of HRQL and a higher BSA, a manifestation in visible areas, and a higher itching intensity. Conclusion This analysis provides data on the distribution of CTCL in routine care. Our study highlights the importance of specific areas, such as visible body areas or the genital area, as determinants for the reduction of HRQL. This knowledge can help to improve patient-centered healthcare in CTCL.